2015
DOI: 10.2147/cia.s60574
|View full text |Cite
|
Sign up to set email alerts
|

Family caregivers’ role implementation at different stages of dementia

Abstract: Purpose: The purpose of this study was to explore family caregivers' role-implementation experiences at different stages of dementia. Patients and methods: For this cross-sectional, exploratory study, 176 dyads of family caregivers and their community-dwelling elderly relatives with dementia were recruited from the neurological clinics of a medical center in Taiwan. The Family Caregiving Inventory was used to assess family caregivers for caregiving activities, role strain, role preparation, and help from other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 36 publications
2
32
0
5
Order By: Relevance
“…Therefore, the prevalence of the female sex is in accordance with the result of other national and international studies (11)(12)(17)(18)(32)(33) . The high average age found was similar to other national studies (14,(34)(35) .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, the prevalence of the female sex is in accordance with the result of other national and international studies (11)(12)(17)(18)(32)(33) . The high average age found was similar to other national studies (14,(34)(35) .…”
Section: Discussionsupporting
confidence: 87%
“…Among these, stand out: those related to clinical conditions of the older adults and their functional capacity; those related to the caregiver, such as female gender, age, low educational level, and feelings of having to fulfill a costly and tense-inducing obligation; and those related to the demands of care, how to live with the older adult, the type of task undertaken, the little emotional, financial and instrumental support they receive, the accumulation of functions, and full-time care (8,(10)(11)(12)(13)(14) . International studies indicate factors influencing overload: the behavioral problems of the older adult, dependence, age of the caregivers, individualization of the family, daily care, inadequate social support, and financial demands (15)(16)(17)(18)(19) . We observed that the process of caring for an older person can reflect negatively in the life of the caregiver.…”
Section: Introductionmentioning
confidence: 99%
“…From examining 62 subjects, they found that the most common symptoms were apathy (71%), aberrant motor behavior (61.3%), sleep problems (56.5%), eating problems (51.6%), and agitation/aggression (45.2%). The combination of dementia and behavior problems compounds the difficulty of care for caregivers (Huang et al, 2015). However, the management of behavioral problems may be diminished with the use of music.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 Perturbação motora, falas repetitivas, distúrbios do sono e outros sintomas, como resistir ou recusar ser cuidado e inquietude também estão entre os aspectos mais problemáticos e angustiantes da prestação de cuidados. 40 O estudo de Huang et al, 41 que investigou o papel do cuidador em cada estágio da doença, identificou que gerenciar os sintomas comportamentais da demência foi a atividade mais difícil desempenhada pelo cuidador em todas as fases da demência.…”
Section: A Relação Entre O Cuidador E Os Sintomas Neuropsiquiátricos unclassified